2017
DOI: 10.1021/acs.jafc.7b00114
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Human Intestinal Bacterium Eggerthella sp. AUH-JLD49s for the Conversion of (−)-3′-Desmethylarctigenin

Abstract: Arctiin is the most abundant bioactive compound contained in the Arctium lappa plant. In our previous study, we isolated one single bacterium capable of bioconverting arctigenin, an aglycone of arctiin, to 3'-desmethylarctigenin (3'-DMAG) solely. However, to date, a specific bacterium capable of producing other arctiin metabolites has not been reported. In this study, we isolated one single bacterium, which we named Eggerthella sp. AUH-JLD49s, capable of bioconverting 3'-DMAG under anaerobic conditions. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…LMG11000, Pseudomonas oleovorans, Eggerthella and Burkholderia, but decreased that from Azoarcus. A recent study by Wang et al (2017) reported that the metabolite by Eggerthella showed an inhibitory effect on growth of human colon cancer line. In addition, the relative abundance of Eggerthella was reduced in Rett syndrome subjects as compared to healthy controls (Strati et al 2016).…”
Section: Genusmentioning
confidence: 99%
“…LMG11000, Pseudomonas oleovorans, Eggerthella and Burkholderia, but decreased that from Azoarcus. A recent study by Wang et al (2017) reported that the metabolite by Eggerthella showed an inhibitory effect on growth of human colon cancer line. In addition, the relative abundance of Eggerthella was reduced in Rett syndrome subjects as compared to healthy controls (Strati et al 2016).…”
Section: Genusmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most frequent cancers, with more than 1.2 million new cases and 500,00 deaths annually around the world, the cornerstones of therapy are surgery, radiotherapy (for patients with rectal cancer), and chemotherapy [ 1 ]. Triptolide, the major active component of Triptergium wilfordii Hook.…”
Section: Introductionmentioning
confidence: 99%
“…The same group has also reported that Blautia sp. AUH-JLD56 could biotransform arctin or arctigenin into 3′-DMAG (Liu et al, 2013;Wang, Yu, et al, 2017). They have evaluated the DPPH radical-scavenging activity of 3′-DMAG (Wang, Solorzano, et al, 2017), yet its anticancer activity remains unknown.…”
Section: Introductionmentioning
confidence: 99%